2020
DOI: 10.1016/j.worlddev.2020.104930
|View full text |Cite
|
Sign up to set email alerts
|

Impact of formal climate risk transfer mechanisms on risk-aversion: Empirical evidence from rural Ethiopia

Abstract: This study examines the effect of smallholder farmers' access to a formal climate risk transfer mechanism on their risk preferences. Survey and experimental data were collected from smallholder farmers that have access to weather index-based crop insurance (WICI) in Ethiopia. We use an endogenous switching (ESP) model to address self-selection and simultaneity bias. Results from the ESP model show that farmers who purchased WICI are less likely to be riskaverse compared with non-purchaser farmers. Similarly, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 76 publications
1
29
0
Order By: Relevance
“…The possible reason for the above dispute is that they ignored the heterogeneity of farmers’ risk aversion. Specifically, Haile et al (2020) considered that small farmers with a strong sense of risk aversion are more inclined to manage climate risks. As the intensity of natural disaster risk increases, farmers with high-risk aversion tend to allocate the family income and labor resources, enhance agricultural investment and family labor and adopt DMF to alleviate low temperatures or drought risk damage.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The possible reason for the above dispute is that they ignored the heterogeneity of farmers’ risk aversion. Specifically, Haile et al (2020) considered that small farmers with a strong sense of risk aversion are more inclined to manage climate risks. As the intensity of natural disaster risk increases, farmers with high-risk aversion tend to allocate the family income and labor resources, enhance agricultural investment and family labor and adopt DMF to alleviate low temperatures or drought risk damage.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The selection of risk aversion attitude is much vital and important under some risky conditions like selection of risk under condition of ambiguity. Because in such condition the decision making can be confusing and definite harms can be bear, thus it is called important choice (Haile, Nillesen, & Tirivayi, 2020). The risk bearing attitude and selection of risky attitude based on the original situation.…”
Section: Risk Aversionmentioning
confidence: 99%
“…Existing literature has studied farmers' adoption of straw return technology from many aspects, such as householder age, gender, education (Ndiritu et al, 2014;Wu and Babcock, 1998), time preference (Mao et al, 2021), technical cognition (Lu et al, 2020), technology subsidies (Kurkalova et al, 2006), media channels and social interaction (Jiang et al, 2021), stability of land tenure (Gao et al, 2018), technical information (Hou et al, 2019), environmental cognition (Sattler and Nagel, 2010), and farm scale (Wu et al, 2018). Some studies have also confirmed that risk preferences are a key factor affecting farmers' adoption of agricultural production technology (Alpizar et al, 2011;Haile et al, 2020). However, few studies have analyzed risk preferences and farmers' adoption of straw return technology from the perspective of productive investment, i.e., whether they invest in new production technology or assets (tractors, in this paper).…”
Section: Introductionmentioning
confidence: 99%